Inhibition of the Inflammasome Signaling Cascade Reduces Alcohol Consumption in Female But Not Male Mice. (9th January 2020) - Lowe, Patrick P.; Cho, Yeonhee; Tornai, David; Coban, Sahin; Catalano, Donna; Szabo, Gyongyi
Abstract : Background: Alcohol use disorder is a significant societal and medical burden that is associated with both organ pathology and addiction. Excessive alcohol use results in neuroinflammation characterized by activation of the inflammasome, a multiprotein complex, and IL‐1β increase in the brain. Recent studies suggest that inflammation could contribute to alcohol addiction. Here, we targeted components of the NOD‐like receptor family pyrin domain containing 3 (NLRP3) inflammasome cascade, which senses and responds to immunologic stimuli, to determine whether NLRP3 inhibition modulates alcohol consumption. Methods: C57BL/6J male and female mice were provided a 2‐bottle choice of alcohol at increasing concentrations (3, 6, 9, and 12%, 4 days each) or water, and some were treated with daily injections of an NLRP3 inhibitor (MCC950), a caspase‐1 inhibitor (VX765), IL‐1 receptor antagonist (IL‐1ra; anakinra), or vehicle injection. Results: Treatment with VX765, MCC950, and IL‐1ra significantly reduced alcohol consumption and preference in female mice ( p < 0.05). Treatment with MCC950 and IL‐1ra reduced alcohol consumption, while IL‐1ra reduced alcohol preference in male mice ( p < 0.05). VX765 did not affect alcohol consumption or preference in male mice. Conclusions: These findings highlight gender differences in alcohol preference and demonstrate that inhibition of different steps in inflammasome signaling can reduce alcohol consumption in females. Inhibition of NLRP3 inflammasome activation and the inflammasome‐IL‐1β cascade opens novel insights into the development of new therapies to address alcohol use disorder in an era of targeted and precision medicine. Abstract : We used inhibitors to target the inflammasome including MCC950 (NLRP3), VX765 (caspase‐1) and anakinra (IL‐1 receptor) and assessed alcohol consumption and preference using a two‐bottle choice paradigm in male and female mice. Treatments reduced alcohol consumption and preference in females with variable affects reducing consumption or preference in males. These findings demonstrate that inhibiting inflammasome signaling can reduce alcohol consumption in females, highlighting gender differences in alcohol preference and providing insight into novel therapies in an era of precision medicine.